2013
DOI: 10.1063/1.4829483
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of graphene adsorbed on WS2 monolayer

Abstract: We perform first-principles calculations to study the energetics and electronic properties of graphene adsorbed on WS2 surface (G/WS2). We find that the graphene can be bound to WS2 monolayer with an interlayer spacing of about 3.9 ´Å with a binding energy of −21–32 meV per carbon atom dependent on graphene adsorption arrangement, suggesting a weak interaction between graphene and WS2. The nearly linear band dispersion character of graphene can be preserved in G/WS2 system, with a sizable band gap, depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
(39 reference statements)
3
16
0
Order By: Relevance
“…21. Due to this weak interaction (physisorption), a small band gap of about 1 meV is obtained, see the zoomed view in Fig.…”
Section: 2mentioning
confidence: 99%
“…21. Due to this weak interaction (physisorption), a small band gap of about 1 meV is obtained, see the zoomed view in Fig.…”
Section: 2mentioning
confidence: 99%
“…The calculated E b of G-WS 2 is À26.9 meV per C atom, which is nearly identical to previously reported values based on the GGA-PBE function (À26.8 meV and À29 meV). 15,55 The E b of G-MoS 2 is À10.2 meV per C atom, which is smaller than the value (À23 meV) reported by Ma et al based on local density approximation (LDA) calculations, 16 which is not surprising given that the LDA method overestimates the calculated results. The binding energies of graphene with (MoS 2 ) 1 /(WS 2 ) 3 , (MoS 2 ) 2 /(WS 2 ) 2 , and (MoS 2 ) 3 /(WS 2 ) 1 lateral heterostructures were À24.1, À18.9, and À14.4 meV, respectively.…”
Section: G-(mos 2 ) X /(Ws 2 ) 4àx Heterostructuresmentioning
confidence: 70%
“…Graphene exhibits a small wrinkle ($0.1 A) in its planar atomic framework for all G-(MoS 2 ) X /(WS 2 ) 4ÀX heterostructures, similar to the previous calculation. 16,26,55 Fig . 4 shows the calculated…”
Section: G-(mos 2 ) X /(Ws 2 ) 4àx Heterostructuresmentioning
confidence: 99%
“…For graphene, several 2D semiconductor or insulator substrates (such as BN [17], MoS 2 [18], C 3 N 4 [19] and WS 2 [20]) have been proposed to support it, suggesting potential applications in graphene-based field effect transistors (FETs). Motivated by this idea, Liu et al [21] investigated silicene deposition on two kinds of semiconductor substrates, hexagonal boron nitride (h-BN) and SiC(0001) surface, and found that the silicene-substrate interaction were energetically in the range of 0.067e0.089 eV per Si atom, within the intensity of typical van der Waals interaction.…”
mentioning
confidence: 99%
“…However, the complicated surface reconstructions of silicene originated from the interaction with the metal substrate often lead to the deformation of configuration for silicene, which can destroy the Dirac feature of FSS [15,16] with the lower carrier mobility and it would hamper the applications of silicene in electronic nanodevices. For graphene, several 2D semiconductor or insulator substrates (such as BN [17], MoS 2 [18], C 3 N 4 [19] and WS 2 [20]) have been proposed to support it, suggesting potential applications in graphene-based field effect transistors (FETs). Motivated by this idea, Liu et al [21] investigated silicene deposition on two kinds of semiconductor substrates, hexagonal boron nitride (h-BN) and SiC(0001) surface, and found that the silicene-substrate interaction were energetically in the range of 0.067e0.089 eV per Si atom, within the intensity of typical van der Waals interaction.…”
mentioning
confidence: 99%